Analysis of blood flow into the main artery via mitral valve - Mohd. Adib, Mohd. Azrul Hisham (2010)
Mitral Valve failure causes death if it is not corrected surgically. Such surgical repair can be improved by understanding mitral biomechanics. A two-dimensional FSI model of the Mitral Valve was generated using the ADINA simulation. A simple approximation of the heart geometry was use, the valve dimensions were based on measurements made. The viscosity of blood and the elastic properties of the valve leaflets were obtained from the literature. In this study, numerical modeling was used to determine the correlation between the degeneration of the Mitral Valves rigidity and backflow problem based on several critical parameters of blood. Two stages of Mitral Valve simulation, systolic and diastolic stage and also with ventricle and without ventricle are investigated. Finally, conclude that rigidity of Mitral Valve antipodes to the backflow and Degeneration causing backflow will reach a constant value and agreed with results from experimental.